Improvement of the technology of flame arrester manufacturing - K. N. Pantyukhova; O. Yu. Bourgonova; Yu. O. Filippov; G. P. Ulyasheva (Омский научный вестник)
When mining hard coal the underground method is prevailed. This method provides a higher quality of the mineral. Methane emissions occur in coal mines during the development of gasbearing seams. These emissions are the reason for the formation of an explosive mixture when mixed with mine air, and also contribute to the spontaneous combustion of coal. Methane alarms are used to monitor the mine atmosphere. Thermocatalytic sensor is the main element of such a gas analyzer. The sensor is placed in a breathable housing. This body is called a flame arrester. This article discusses the possibility of replacing the material used for the manufacture of a flame arrester. The basis of the existing material is nickel powder. It is proposed to replace it with a cermet bond. The composition of the ceramic material of the part is developed by the author and presented in the article. Replacement of material will lead to a significant reduction in the cost of the part and simplification of the manufacturing technology.